A Review of Cerebral Hemodynamics During Sleep Using Near-Infrared Spectroscopy - Ren, Haoran; Jiang, Xinyu; Xu, Ke; Chen, Chen; Yuan, Yafei; Dai, Chenyun; Chen, Wei (Frontiers in Neurology, 2020)
Investigating cerebral hemodynamic changes during regular sleep cycles and sleep disorders is fundamental for understanding the nature of physiological and pathological mechanisms in the regulation of cerebral oxygenation during sleep. The combination of polysomnography (PSG) with near-infrared spectroscopy (NIRS) provides complementary insights into cerebral hemodynamic changes in response to sleep events at the cortical level. This paper presents a brief historical overview of the sleep studies using NIRS, investigating the cerebral hemodynamic changes associated with different sleep states in healthy populations, and fluctuation of cerebral hemodynamics in response to sleep disorders in patients with mild to acute sleep-disordered breathing. In regular sleep, the use of grand averaged values at specific sleep stages to compare changes in cerebral hemodynamics between different sleep stages and transient hemodynamic patterns during the transition of sleep stages are introduced. Moreover, the impact of different sleep-disordered breathing events on cerebral hemodynamics, physiological factors affecting cerebral hemodynamics during sleep-disordered breathing, comparison and relations between cerebral oxygenation and systemic oxygen, and the evaluation of treatment efficacy of positive airway pressure therapy have been reviewed. Meanwhile, the physiological and pathological mechanisms, including cerebrovascular autonomic regulation and the regulation mechanism between peripheral oxygenation and cerebral oxygenation, were discussed. However, discrepancy results existed across studies. Thus, the variety in experimental designs and signal processing method are further discussed in this review. Finally, the paper concludes with the possible future clinical applications and the possible direction for further sophisticated NIRS interpretation and analysis.